Distinct patterns of activated neurons throughout the rat midbrain periaqueductal gray induced by chemical stimulation within its subdivisions - Sandkühler, Jürgen; Herdegen, Thomas (The journal of comparative neurology, 1995)
This study provides a map of those neurons in the midbrain periaqueductal gray which are activated by chemical stimulation within different subdivisions of the periaqueductal gray. In pentobarbital anesthetized rats, the expression of the c-FOS protein was detected by immunocytochemistry and was used as a marker of neuronal activity. Microinjections of the γ-aminobutyric acid (GABAA) receptor antagonist bicuculline (200 pmol in 50 nl) were used to increase selectively the firing rate of neurons originating from the injection site. The pattern of c-FOS immunoreactivity was highly specific for different injection sites. Dorsal injections were characterized by an extensive distribution of c-FOS immunoreactivity along the entire rostrocaudal extent of the periaqueductal gray, while ventral injections produced a much more restricted labeling. Following injection into the dorsal subdivision of the rostral periaqueductal gray, c-FOS immunoreactivity was present bilaterally in the dorsal and dorsolateral subdivisions of the rostral periaqueductal gray and was found in all subdivisions of the caudal periaqueductal gray. Dorsolateral injections at the level of the oculomotor nuclei produced strictly ipsilateral labeling in the dorsal and dorsolateral periaqueductal gray at the level of injection and throughout the ipsilateral half of the periaqueductal gray at more caudal levels. Stimulation in the ventrolateral periaqueductal gray induced FOS in the ventrolateral periaqueductal gray and the adjoining reticular formation. At rostral levels c-FOS immunoreactivity was also seen in the lateral periaqueductal gray but was absent caudal to the injection site. The identified patterns of activity in the periaqueductal gray provide a new basis for the interpretation of the diverse functional consequences of stimulation at periaqueductal gray sites. © 1995 Wiley-Liss, Inc.